Genetic variation of wood and resin production in Pinus caribaea var. hondurensis Barret & Golfari - Santos, Wanderley dos [UNESP]; Lemos Souza, Danilla Cristina; Teixeira de Moraes, Mario Luiz [UNESP]; Aguiar, Ananda Virginia de (Johann Heinrich Von Thunen Inst-vti, 2016)
The purpose of this work was to estimate genetic parameters and selection gain of Pinus caribaea var. hondurensis progeny trial for wood and resin production as well as correlation between them. Experiment was established in complete lattice square 10 x 10 (triple), 100 treatments, 10 plants per plot, 3 m x 3 m spacing. Twelve years after planting the trial had thinned considerably leaving six plants per plot. Twenty-seven years after planting height, diameter at breast height (dbh) and resin production were measured. Deviance analysis, genetic parameter estimates, selection expected gain, genetic and phenotypic correlation were based on REML/BLUP method. Significant phenotypic differences were observed among and within families for all traits. The thinning at 12 years after planting, contributed positively to dbh increase and resin production, with an average of 30.60 cm and 4.83 kg tree(-1)year(-1). The individual narrow sense heritability ranged from 0.25 to 0.38 for dbh and volume. Genetic and phenotypic correlation between growth traits were positive, and significant. Therefore, different selection strategies will be proposed separately for both traits (resin and wood). The selection gains were significant, especially with 10 % selection intensity (individual selection) for dbh (7.53 %) and resin (13.49 %). The trial has had good performance for growth, resin and genetic variability to support the next breeding generation.
Keywords: heritability; genetic breeding; pine and seed production